Environment, management, and genetic contributions to maize kernel hardness and grain yield - Cerrudo, Aníbal Alejandro; Martinez, Dionisio Roberto; Izquierdo, Natalia Gabriela; Cirilo, Alfredo Gabriel; Laserna, Paula; Reinoso, Lucio; Valentinuz, Oscar Rodolfo; Balbi, Celsa Noemí; Andrade, Fernando Hector (2018)
Dry milling performance of maize (Zea mays L.) is directly related to kernel hardness. This study assessed the contribution of maize hybrid and crop growing condition on kernel hardness and grain yield. Three hybrids that fully explore the available genetic variability for kernel hardness were planted at different environments across the Argentinean cropping area. At each environment, early and late planting dates and supplemental fertilization were evaluated. Kernel coarse-to-fine ratio was used as an indicator of kernel hardness. Coarse-to-fine ratio ranged from 2.0 to 7.0 g g−1, grain yield ranged from 494 to 1391 g m−2, and both were affected by hybrid and growing conditions. Hybrid ranking was stable across growing conditions; however, differences among hybrids in kernel coarse-to-fine ratio and grain yield increased when growing condition favored kernel hardness and grain yield. Growing condition explained >60% of total variability in coarse- to- fine ratio and grain yield. Fertilization management had significant but small influence on assessed variables. In contrast, the interaction between planting date and environment was the major determinant of kernel coarse-to-fine ratio and grain yield. Delayed planting consistently reduced kernel hardness at high-latitude locations. Potential photosynthetic source during maize reproductive period explained 37% of the variation in kernel coarse-to-fine ratio. Environment and agronomic management should be considered together with the hybrid in the design of maize production strategies oriented to end-use quality.